Studi Kandungan Bahan Organik Dan Mineral (N, P, K, Fe dan Mg) Sedimen Di Kawasan Mangrove Desa Bedono, Kecamatan Sayung, Kabupaten Demak - Nugroho, Radich Arief; Widada, Sugeng; Pribadi, Rudhi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Mangroves in Bedono Village, District Sayung, Demak Regency considered as degraded mainly due to land conversion and reclamation which lead to coastal erosion and permanent flooding. This mangroves condition, in conjuction with the exsistance of several estuaries believes in some part controlled sedimentation and related process in the area including sediment particle size, organic and mineral (N, P, K,Fe and Mg) distribution. The study was aimed to determine distribution of organic and mineral (N, P, K,Fe and Mg) of mangrove sediment in Bedono Village, District Sayung, Demak Regency, and conducted between May-July 2010. A purposive sampling base descriptive method was applied for this study, and sediment samples were analysed at Geological Laboratory (Marine Science Department) Faculty of Fisheries and Marine Sciences and Chemical Analytical Laboratory (Chemical Department), Faculty of Science and Mathematics, Diponegoro University. The result showed that sediment organic content of Tunjung Sari (15,42%) and Gonjol (16,46%) were slightly higer than in Sayung (12,48%) and Soban (12,06%), N content in Tunjung Sari (0,46%) and Soban (0,43%) much higher than in Gonjol (0,27%) and Sayung (0,29%), while P content in Gonjol (354,73 mg/kg) was the highest followed by Tunjung Sari (245,60 mg/kg) and Sayung (203,43 mg/kg) and the lowest was in Soban (80,42 mg/kg). The rate of sediment K content, similar to N content, was high in Tunjung Sari (0,50%) and Soban (0,54%) and lower in Gonjol (0,39%) and Sayung (0,35%). Fe content was higher in Gonjol (5,52 %) than in Tunjung Sari (3,93 %), Sayung (2,55 %) and Soban (3,92 %), meanwhile Mg content was higher in Tunjung Sari (0,125 %) than Gonjol (0,075 %), Sayung (0,080 %) and Soban (0,006 %).